А problem of arboreal raw material is in Europe and Ukraine - Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2007)
The sources of raw materials of wood are analysed in Ukraine and Europe. Grounded, that the potential resources of arboreal raw material are wastes of cutting areas, wastes of woodworking productions and of used wood. A diagram is offered of rational appeal of material-financial resources of, which characterizes its complex use.